Question and Answers Forum

None Questions

Question Number 105266 by mohammad17 last updated on 27/Jul/20

Answered by mathmax by abdo last updated on 27/Jul/20

$$\mathrm{we}\:\mathrm{have}\:\mathrm{L}\left(\mathrm{t}^{\frac{\mathrm{3}}{\mathrm{2}}} \right)\:=\int_{\mathrm{0}} ^{\infty} \:\mathrm{x}^{\frac{\mathrm{3}}{\mathrm{2}}} \:\mathrm{e}^{−\mathrm{tx}} \mathrm{dx}\:=_{\mathrm{tx}\:=\mathrm{u}} \:\:\int_{\mathrm{0}} ^{\infty} \:\:\left(\frac{\mathrm{u}}{\mathrm{t}}\right)^{\frac{\mathrm{3}}{\mathrm{2}}} \:\mathrm{e}^{−\mathrm{u}} \:\frac{\mathrm{du}}{\mathrm{t}} \\$$$$=\frac{\mathrm{1}}{\mathrm{t}^{\frac{\mathrm{3}}{\mathrm{2}}+\mathrm{1}} }\int_{\mathrm{0}} ^{\infty} \:\mathrm{u}^{\frac{\mathrm{3}}{\mathrm{2}}} \:\mathrm{e}^{−\mathrm{u}} \:\mathrm{du}\:=\frac{\mathrm{1}}{\mathrm{t}^{\frac{\mathrm{5}}{\mathrm{2}}} }\:\int_{\mathrm{0}} ^{\infty} \:\mathrm{u}^{\frac{\mathrm{5}}{\mathrm{2}}−\mathrm{1}} \:\mathrm{e}^{−\mathrm{u}} \mathrm{du}\:=\frac{\Gamma\left(\frac{\mathrm{5}}{\mathrm{2}}\right)}{\mathrm{t}^{\frac{\mathrm{5}}{\mathrm{2}}} } \\$$$$\Gamma\left(\frac{\mathrm{5}}{\mathrm{2}}\right)\:=\Gamma\left(\frac{\mathrm{3}}{\mathrm{2}}+\mathrm{1}\right)\:=\frac{\mathrm{3}}{\mathrm{2}}\Gamma\left(\frac{\mathrm{3}}{\mathrm{2}}\right)\:=\frac{\mathrm{3}}{\mathrm{2}}\Gamma\left(\frac{\mathrm{1}}{\mathrm{2}}+\mathrm{1}\right)\:=\frac{\mathrm{3}}{\mathrm{4}}\Gamma\left(\frac{\mathrm{1}}{\mathrm{2}}\right) \\$$$$\Gamma\left(\frac{\mathrm{1}}{\mathrm{2}}\right)\:=\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{2}}−\mathrm{1}} \:\mathrm{e}^{−\mathrm{t}} \:\mathrm{dt}\:=\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{e}^{−\mathrm{t}} }{\sqrt{\mathrm{t}}}\mathrm{dt}\:=_{\sqrt{\mathrm{t}}=\mathrm{u}} \:\:\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{e}^{−\mathrm{u}^{\mathrm{2}} } }{\mathrm{u}}\left(\mathrm{2u}\right)\mathrm{du} \\$$$$=\mathrm{2}\int_{\mathrm{0}} ^{\infty} \:\mathrm{e}^{−\mathrm{u}^{\mathrm{2}} } \mathrm{du}\:=\sqrt{\pi}\:\Rightarrow\mathrm{L}\left(\mathrm{t}^{\frac{\mathrm{3}}{\mathrm{2}}} \right)\:=\frac{\mathrm{3}}{\mathrm{4}}×\frac{\sqrt{\pi}}{\mathrm{t}^{\frac{\mathrm{5}}{\mathrm{2}}} } \\$$

Answered by abdomathmax last updated on 27/Jul/20

$$\mathrm{L}\left(\mathrm{h}\left(\mathrm{s}\right)\right)=\int_{\mathrm{0}} ^{\infty} \mathrm{t}^{\mathrm{2}} \mathrm{sin}\left(\mathrm{2t}\right)\mathrm{e}^{−\mathrm{st}} \mathrm{dt} \\$$$$=\mathrm{Im}\left(\int_{\mathrm{0}} ^{\infty} \mathrm{t}^{\mathrm{2}} \:\mathrm{e}^{\mathrm{2it}−\mathrm{st}} \mathrm{dt}\right)\:=\mathrm{Im}\left(\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\mathrm{2}} \:\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \mathrm{dt}\right)\:\mathrm{but}\:\mathrm{by}\:\mathrm{parts} \\$$$$\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\mathrm{2}} \:\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \mathrm{dt}\:\:=\left[\frac{\mathrm{t}^{\mathrm{2}} }{\mathrm{2i}−\mathrm{s}}\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \right]_{\mathrm{t}=\mathrm{0}} ^{\infty} −\int_{\mathrm{0}} ^{\infty} \mathrm{2t}\:.\frac{\mathrm{1}}{\mathrm{2i}−\mathrm{s}}\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \mathrm{dt} \\$$$$=−\frac{\mathrm{2}}{\mathrm{2i}−\mathrm{s}}\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}\:\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \:\mathrm{dt} \\$$$$=\frac{−\mathrm{2}}{\mathrm{2i}−\mathrm{s}}\left\{\:\left[\frac{\mathrm{t}}{\mathrm{2i}−\mathrm{s}}\:\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \right]_{\mathrm{0}} ^{\infty} −\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{1}}{\mathrm{2i}−\mathrm{s}}\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \mathrm{dt}\right\} \\$$$$=\frac{\mathrm{2}}{\left(\mathrm{2i}−\mathrm{s}\right)^{\mathrm{2}} }\int_{\mathrm{0}} ^{\infty} \:\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \mathrm{dt}\:=\frac{\mathrm{2}}{\left(\mathrm{2i}−\mathrm{s}\right)^{\mathrm{2}} }\left[\frac{\mathrm{1}}{\mathrm{2i}−\mathrm{s}}\mathrm{e}^{\left(\mathrm{2i}−\mathrm{s}\right)\mathrm{t}} \right]_{\mathrm{0}} ^{\infty} \\$$$$=−\frac{\mathrm{2}}{\left(\mathrm{2i}−\mathrm{s}\right)^{\mathrm{3}} }\:=\frac{\mathrm{2}}{\left(\mathrm{s}−\mathrm{2i}\right)^{\mathrm{3}} }\:=\frac{\mathrm{2}\left(\mathrm{s}+\mathrm{2i}\right)^{\mathrm{3}} }{\left(\mathrm{s}^{\mathrm{2}} \:+\mathrm{4}\right)^{\mathrm{3}} } \\$$$$=\frac{\mathrm{2}\left(\mathrm{s}^{\mathrm{3}} \:+\mathrm{3s}^{\mathrm{2}} \left(\mathrm{2i}\right)\:+\mathrm{3s}\left(\mathrm{2i}\right)^{\mathrm{2}} \:+\left(\mathrm{2i}\right)^{\mathrm{3}} \right)}{\left(\mathrm{s}^{\mathrm{2}} \:+\mathrm{4}\right)^{\mathrm{3}} } \\$$$$=\frac{\mathrm{2}\left(\mathrm{s}^{\mathrm{3}\:} \:+\mathrm{6is}^{\mathrm{2}} \:−\mathrm{12s}−\mathrm{8i}\right)}{\left(\mathrm{s}^{\mathrm{2}} \:+\mathrm{4}\right)^{\mathrm{3}} }\:\Rightarrow \\$$$$\mathrm{Im}\left(...\right)\:=\frac{\mathrm{2}\left(\mathrm{6s}^{\mathrm{2}} −\mathrm{8}\right)}{\left(\mathrm{s}^{\mathrm{2}} \:+\mathrm{4}\right)^{\mathrm{3}} }\:\Rightarrow\:\mathrm{F}\left(\mathrm{s}\right)\:=\frac{\mathrm{4}\left(\mathrm{3s}^{\mathrm{2}} −\mathrm{4}\right)}{\left(\mathrm{s}^{\mathrm{2}} \:+\mathrm{4}\right)^{\mathrm{3}} } \\$$$$\\$$

Answered by Aziztisffola last updated on 27/Jul/20

$$\left.\mathrm{A}\right)\:\mathrm{F}\left(\mathrm{s}\right)=\left(−\mathrm{1}\right)^{\mathrm{2}} \frac{\mathrm{d}^{\mathrm{2}} }{\mathrm{ds}^{\mathrm{2}} }\mathrm{L}\left(\mathrm{sin2t}\right)=\frac{\mathrm{d}^{\mathrm{2}} }{\mathrm{ds}^{\mathrm{2}} }\mathrm{L}\left(\mathrm{sin2t}\right) \\$$$$=\frac{\mathrm{d}^{\mathrm{2}} }{\mathrm{ds}^{\mathrm{2}} }\left(\frac{\mathrm{2}}{\mathrm{s}^{\mathrm{2}} +\mathrm{4}}\right)=\frac{\mathrm{d}}{\mathrm{ds}}\left(\frac{−\mathrm{4s}}{\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)^{\mathrm{2}} }\right)=\frac{−\mathrm{4}\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)^{\mathrm{2}} +\mathrm{4s}.\mathrm{2s}\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)}{\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)^{\mathrm{4}} } \\$$$$=\frac{−\mathrm{4}\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)+\:\mathrm{8s}^{\mathrm{2}} }{\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)^{\mathrm{3}} }=\frac{\mathrm{4s}^{\mathrm{2}} −\mathrm{16}}{\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)^{\mathrm{3}} } \\$$$$\:\mathrm{F}\left(\mathrm{s}\right)=\frac{\mathrm{4s}^{\mathrm{2}} −\mathrm{16}}{\left(\mathrm{s}^{\mathrm{2}} +\mathrm{4}\right)^{\mathrm{3}} } \\$$

Answered by bemath last updated on 27/Jul/20

Answered by Aziztisffola last updated on 27/Jul/20

$$\left(\mathrm{B}\right)\:\mathrm{L}\left(\mathrm{t}^{\frac{\mathrm{3}}{\mathrm{2}}} \right)=\mathrm{L}\left(\mathrm{t}\sqrt{\mathrm{t}}\right)=−\frac{\mathrm{d}}{\mathrm{ds}}\mathrm{L}\left(\sqrt{\mathrm{t}}\right)=−\left(\frac{\sqrt{\pi}}{\mathrm{2}\sqrt{\mathrm{s}^{\mathrm{3}} }}\right)' \\$$$$=−\frac{\sqrt{\pi}}{\mathrm{2}}\left(\frac{\mathrm{1}}{\sqrt{\mathrm{s}^{\mathrm{3}} }}\right)'=\frac{\mathrm{3}\sqrt{\pi}}{\mathrm{4}}\frac{\mathrm{s}}{\sqrt{\mathrm{s}}}=\frac{\mathrm{3}\sqrt{\pi}}{\mathrm{4}}\sqrt{\mathrm{s}} \\$$$$\:\mathrm{L}\left(\mathrm{t}^{\frac{\mathrm{3}}{\mathrm{2}}} \right)=\frac{\mathrm{3}\sqrt{\pi}}{\mathrm{4}}\sqrt{\mathrm{s}} \\$$

Answered by mathmax by abdo last updated on 27/Jul/20

$$\left.\mathrm{b}\right)\mathrm{x}\left(\mathrm{y}+\mathrm{2}\right)\mathrm{y}^{'} \:=\mathrm{lnx}\:+\mathrm{1}\:\mathrm{andy}\left(\mathrm{1}\right)=−\mathrm{1} \\$$$$\left(\mathrm{y}+\mathrm{2}\right)\mathrm{y}^{'} \:\:=\frac{\mathrm{lnx}+\mathrm{1}}{\mathrm{x}}\:\Rightarrow\int\left(\mathrm{y}+\mathrm{2}\right)\mathrm{y}^{'} \:\mathrm{dy}\:=\int\frac{\mathrm{lnx}+\mathrm{1}}{\mathrm{x}}\mathrm{dx}\:\:\Rightarrow \\$$$$\frac{\mathrm{1}}{\mathrm{2}}\mathrm{y}^{\mathrm{2}} \:+\mathrm{2y}\:=\mathrm{ln}\mid\mathrm{x}\mid\:+\int\:\frac{\mathrm{lnx}}{\mathrm{x}}\mathrm{dx}\:\Rightarrow\mathrm{y}^{\mathrm{2}} \:+\mathrm{4y}\:−\mathrm{2}\left\{\mathrm{ln}\mid\mathrm{x}\mid+\int\:\frac{\mathrm{lnx}}{\mathrm{x}}\mathrm{dx}\right\}=\mathrm{0} \\$$$$\Delta^{'} \:=\mathrm{4}+\mathrm{2}\left\{\mathrm{ln}\mid\mathrm{x}\mid+\int\:\frac{\mathrm{lnx}}{\mathrm{x}}\mathrm{dx}\right\}\:\Rightarrow\:\mathrm{y}\:=−\mathrm{2}\:\overset{−} {+}\sqrt{\mathrm{ln}\mid\mathrm{x}\mid+\int\frac{\mathrm{lnx}}{\mathrm{x}}\mathrm{dx}} \\$$

Commented by abdomathmax last updated on 27/Jul/20

$$\mathrm{but}\:\int\:\frac{\mathrm{lnx}}{\mathrm{x}}\mathrm{dx}\:=\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ln}^{\mathrm{2}} \mathrm{x}\:+\mathrm{c}\:\Rightarrow \\$$$$\mathrm{y}\:=−\mathrm{2}\overset{−} {+}\sqrt{\mathrm{ln}\mid\mathrm{x}\mid+\frac{\mathrm{ln}^{\mathrm{2}} \mathrm{x}}{\mathrm{2}}+\mathrm{c}} \\$$

Answered by Aziztisffola last updated on 27/Jul/20

$$\left.\mathrm{A}\right)\:\mathrm{2x}\sqrt{\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} }\:\mathrm{y}'=\mathrm{1}+\mathrm{2x}\sqrt{\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} } \\$$$$\left(\mathrm{2x}−\left(\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} \right)'\right)\sqrt{\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} }=\mathrm{1}+\mathrm{2x}\sqrt{\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} } \\$$$$−\left(\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} \right)'\sqrt{\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} }=\mathrm{1} \\$$$$−\frac{\mathrm{x}−\mathrm{yy}'}{\sqrt{\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} }}\sqrt{\mathrm{x}^{\mathrm{2}} −\mathrm{y}^{\mathrm{2}} }=\mathrm{1} \\$$$$\mathrm{yy}'=\mathrm{x}+\mathrm{1}\:\Rightarrow\int\mathrm{yy}'\mathrm{dx}=\int\left(\mathrm{x}+\mathrm{1}\right)\mathrm{dx} \\$$$$\frac{\mathrm{y}^{\mathrm{2}} }{\mathrm{2}}=\frac{\mathrm{x}^{\mathrm{2}} }{\mathrm{2}}+\mathrm{x}+\mathrm{c}\:\Rightarrow\mathrm{y}=\underset{−} {+}\sqrt{\mid\mathrm{x}^{\mathrm{2}} +\mathrm{2x}+\mathrm{C}\mid} \\$$

Answered by Aziztisffola last updated on 27/Jul/20

$$\left.\mathrm{B}\right) \\$$$$\mathrm{x}\left(\mathrm{y}+\mathrm{2}\right)\mathrm{y}'=\mathrm{lnx}+\mathrm{1}\Leftrightarrow\left(\mathrm{y}+\mathrm{2}\right)\mathrm{y}'=\mathrm{lnx}/\mathrm{x}+\mathrm{1}/\mathrm{x} \\$$$$\mathrm{yy}'+\mathrm{2y}'=\frac{\mathrm{lnx}}{\mathrm{x}}+\frac{\mathrm{1}}{\mathrm{x}}\Rightarrow\int\left(\mathrm{yy}'+\mathrm{2y}'\right)\mathrm{dx}=\int\left(\frac{\mathrm{lnx}}{\mathrm{x}}+\frac{\mathrm{1}}{\mathrm{x}}\right)\mathrm{dx} \\$$$$\frac{\mathrm{1}}{\mathrm{2}}\mathrm{y}^{\mathrm{2}} +\mathrm{2y}=\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ln}^{\mathrm{2}} \left(\mathrm{x}\right)+\mathrm{lnx}+\mathrm{C} \\$$$$\frac{\mathrm{1}}{\mathrm{2}}\mathrm{y}^{\mathrm{2}} \left(\mathrm{1}\right)+\mathrm{2y}\left(\mathrm{1}\right)=\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ln}^{\mathrm{2}} \left(\mathrm{1}\right)+\mathrm{ln}\left(\mathrm{1}\right)+\mathrm{C} \\$$$$\frac{\mathrm{1}}{\mathrm{2}}−\mathrm{2}=\mathrm{C}\Rightarrow\mathrm{C}=−\frac{\mathrm{3}}{\mathrm{2}} \\$$$$\frac{\mathrm{1}}{\mathrm{2}}\mathrm{y}^{\mathrm{2}} +\mathrm{2y}=\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ln}^{\mathrm{2}} \left(\mathrm{x}\right)+\mathrm{lnx}−\frac{\mathrm{3}}{\mathrm{2}} \\$$$$\Leftrightarrow\mathrm{y}^{\mathrm{2}} +\mathrm{4y}=\mathrm{ln}^{\mathrm{2}} \left(\mathrm{x}\right)+\mathrm{2lnx}−\mathrm{3} \\$$$$\Leftrightarrow\mathrm{y}^{\mathrm{2}} +\mathrm{4y}+\mathrm{4}=\mathrm{ln}^{\mathrm{2}} \left(\mathrm{x}\right)+\mathrm{2lnx}+\mathrm{1} \\$$$$\Leftrightarrow\left(\mathrm{y}+\mathrm{2}\right)^{\mathrm{2}} =\mathrm{ln}^{\mathrm{2}} \left(\mathrm{x}\right)+\mathrm{2lnx}+\mathrm{1} \\$$$$\Rightarrow\mathrm{y}=\underset{−} {+}\sqrt{\mid\mathrm{ln}^{\mathrm{2}} \left(\mathrm{x}\right)+\mathrm{2lnx}+\mathrm{1}\mid}\:−\mathrm{2} \\$$

Answered by abdomathmax last updated on 27/Jul/20

$$\mathrm{y}^{''} −\mathrm{6y}^{'} \:−\mathrm{7y}\:=\mathrm{13cos}\left(\mathrm{2t}\right)+\mathrm{34sin}\left(\mathrm{2t}\right) \\$$$$\mathrm{h}\rightarrow\mathrm{r}^{\mathrm{2}} −\mathrm{6r}−\mathrm{7}\:=\mathrm{0} \\$$$$\Delta^{'} \:=\mathrm{9}+\mathrm{7}\:=\mathrm{16}\:\Rightarrow\mathrm{r}_{\mathrm{1}} =\mathrm{3}+\mathrm{4}\:=\mathrm{7}\:\mathrm{and}\:\mathrm{r}_{\mathrm{2}} =\mathrm{3}−\mathrm{4}\:=−\mathrm{1}\:\Rightarrow \\$$$$\mathrm{y}_{\mathrm{h}} =\mathrm{a}\:\mathrm{e}^{\mathrm{7x}} \:+\mathrm{be}^{−\mathrm{x}} \:=\mathrm{au}_{\mathrm{1}} \:+\mathrm{bu}_{\mathrm{2}} \\$$$$\mathrm{W}\left(\mathrm{u}_{\mathrm{1}} \:,\mathrm{u}_{\mathrm{2}} \right)\:=\begin{vmatrix}{\mathrm{e}^{\mathrm{7x}} \:\:\:\:\:\:\:\:\mathrm{e}^{−\mathrm{x}} }\\{\mathrm{7e}^{\mathrm{7x}} \:\:\:\:\:\:\:−\mathrm{e}^{−\mathrm{x}} }\end{vmatrix}=−\mathrm{e}^{\mathrm{6x}} −\mathrm{7e}^{\mathrm{6x}} \:=−\mathrm{8e}^{\mathrm{6x}} \:\neq\mathrm{0} \\$$$$\mathrm{W}_{\mathrm{1}} =\begin{vmatrix}{\mathrm{o}\:\:\:\:\:\:\:\:\:\:\mathrm{e}^{−\mathrm{x}} }\\{\mathrm{13cos}\left(\mathrm{2x}\right)+\mathrm{34sin}\left(\mathrm{2x}\right)\:\:\:\:−\mathrm{e}^{−\mathrm{x}} }\end{vmatrix} \\$$$$=−\mathrm{e}^{−\mathrm{x}} \left(\mathrm{13cos}\left(\mathrm{2x}\right)+\mathrm{34sin}\left(\mathrm{2x}\right)\right) \\$$$$\mathrm{W}_{\mathrm{2}} =\begin{vmatrix}{\mathrm{e}^{\mathrm{7x}} \:\:\:\:\:\:\:\:\mathrm{0}}\\{\mathrm{7e}^{\mathrm{7x}} \:\:\:\:\:\:\mathrm{13cos}\left(\mathrm{2x}\right)\:+\mathrm{34sin}\left(\mathrm{2x}\right)}\end{vmatrix} \\$$$$=\mathrm{e}^{\mathrm{7x}} \left(\mathrm{13}\:\mathrm{cos}\left(\mathrm{2x}\right)+\mathrm{34}\:\mathrm{sin}\left(\mathrm{2x}\right)\right. \\$$$$\mathrm{v}_{\mathrm{1}} =\int\:\frac{\mathrm{w}_{\mathrm{1}} }{\mathrm{w}}\mathrm{dx}\:=−\int\:\:\frac{\mathrm{e}^{−\mathrm{x}} \left\{\mathrm{13cos}\left(\mathrm{2x}\right)+\mathrm{34}\:\mathrm{sin}\left(\mathrm{2x}\right)\right\}}{−\mathrm{8e}^{\mathrm{6x}} }\mathrm{dx} \\$$$$=\frac{\mathrm{1}}{\mathrm{8}}\int\:\:\mathrm{e}^{−\mathrm{7x}} \left\{\mathrm{13cos}\left(\mathrm{2x}\right)+\mathrm{34sin}\left(\mathrm{2x}\right)\right\}\mathrm{dx}\:=... \\$$$$\mathrm{v}_{\mathrm{2}} =\int\:\frac{\mathrm{w}_{\mathrm{2}} }{\mathrm{w}}\mathrm{dx}\:=\int\:\frac{\mathrm{e}^{\mathrm{7x}} \left\{\mathrm{13cos}\left(\mathrm{2x}\right)+\mathrm{34}\:\mathrm{sin}\left(\mathrm{2x}\right)\right\}}{−\mathrm{8e}^{\mathrm{6x}} }\mathrm{dx} \\$$$$=−\frac{\mathrm{1}}{\mathrm{8}}\:\int\:\mathrm{e}^{\mathrm{x}} \left\{\mathrm{13cos}\left(\mathrm{2x}\right)+\mathrm{34sin}\left(\mathrm{2x}\right)\right\}\mathrm{dx}\:=... \\$$$$\Rightarrow\mathrm{y}_{\mathrm{p}} =\mathrm{u}_{\mathrm{1}} \mathrm{v}_{\mathrm{1}} \:+\mathrm{u}_{\mathrm{2}} \mathrm{v}_{\mathrm{2}} \:\:\mathrm{and}\:\mathrm{general}\:\mathrm{solution}\:\mathrm{is} \\$$$$\mathrm{y}\:=\mathrm{y}_{\mathrm{h}} \:+\mathrm{y}_{\mathrm{p}} \\$$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com